UMP establishes strategic collaboration with Piri Reis University, Turkiye - Mohd Ferdaus, Musa (2023)
ISTANBUL, 27 February 2023 - Universiti Malaysia Pahang (UMP) continues to strengthen its global brand through a new strategic partnership with Piri Reis University (PRU) in Turkiye.